Comparison of elderly and young onset rheumatoid arthritis - N. Jaouad; B. Amine; I. Elbinoune; S. Rostom; R. Bahiri (Verduci Editore, 2022)
Objective: To describe demographic, clinical, paraclinical and therapeutic characteristics of elderly onset (EORA) compared to young-onset (YORA) rheumatoid arthritis. Patients and Methods: We studied 50 EORA and 100 YORA. Socio-demographic characteristics, clinical and paraclinical data of the disease were collected as well as the treatments assigned to patients. EORA patients were defined as disease onset ≥ 60 years. Results: At the study visit, EORA patients had a mean age of 68.3 ± 6.4 years old and YORA patients were aged 42.5 ± 9.1 years old. A male predominance was noted in EORA group than the YORA group (38% vs. 12%, p <0.001). The onset of disease in EORA was more acute (p <0.001) with more systemic symptoms (p <0.001). EORA patients had higher Disease Activity Score of 28 joints (DAS28) (p=0.03) and higher erythrocyte sedimentation rate (ESR) (40 [10-110] vs. 28 [2-88], p=0.015). There was no significant difference in seropositive character, prevalence of radiographic erosions or joint deformity. The EORA patients had a higher Health Assessment Questionnaire (HAQ) (1 [0.4-2.2] vs. 0.6 [0.2-2], p<0.001) and more comorbidities (84% vs. 37%, p<0.001). Methotrexate was the most conventional synthetic disease-modifying antirheumatic drugs used in the two groups (95% in the YORA and 96% in the EORA; p=0.740). The EORA group received fewer biologic drugs than the YORA group (30% vs. 47 %; p=0.041). Conclusions: There were more male in EORA group. Activity and HAQ was higher in the EORA group. The EORA had more comorbidities which may explain the lesser use of biological treatments.